Análise dos discursos acadêmicos da/sobre a voz cantada no processo de ensino-aprendizagem. - Santana, José Reginaldo Gomes de (2019)
This research has as general objective to analyze the academic discourses on / onf the production of the sung voice in the teaching-learning process. The specific objectives are: To identify the speeches about the singing voice that circulate in the academic environment of courses of Licenciatura in Music; To identify, in academic discourses, identity affirmations and ideological interpellations that position the subject in front of the established ways of singing in the teaching-learning process; to analyze the functioning of the materiality of the voice sung in the teaching-learning process. This research is of a qualitative nature and developed through theoreticalmethodological procedures of French Discourse Analysis, affiliated with the thought of Michel Pêcheux and with theoretical and methodological developments in Brazil from Eni Orlandi's studies. Among the theoretical-methodological framework of Discourse Analysis, the concepts of discursive formations, identification, counter-identification, delimitation, discursive memory, vocal sounds and discursivity of the body will be mobilized. The research was carried out with students and teachers in Licentiate degree courses in Music with qualification in popular singing and courses with curricula that prioritize the erudite music. The selection of participants for this study is related to subjects who experience the construction of knowledge in the subjects of popular singing and vocal technique. The corpus came from semi-structured interviews and singing auditions. As for discursive functioning, it has been identified that the imbrication of what is discursive, of what is signified in history, with what is individual, unique, timbristic produces discourses and / or imagistic illusions of identification with the voice of the other, identification and counter-identification of the subject with the discursive formations of the vocal technique.